Decay of correlations for weakly expanding dynamical systems with Dini potentials under optimal quasi-gap condition. (22nd December 2021) - Jiang, Yunping; Ye, Yuan-Ling
Abstract: We find an optimal quasi-gap condition for a weakly expanding dynamical system associated with Dini potential. Under this optimal quasi-gap condition, we prove the Ruelle operator theorem and further the decay of the correlations for any weakly expanding dynamical systems with Dini potentials.